2015
DOI: 10.1007/s11746-015-2596-5
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Subcritical Carbon Dioxide Extraction and Bran Stabilization Methods on Rice Bran Oil

Abstract: a promising method to produce premium-quality rice bran oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 42 publications
1
14
3
Order By: Relevance
“…Results indicated the tocol composition of avocado oil was significantly affected ( p < 0.05) by extraction methods, whereby the contents of α‐ and γ‐tocopherols of SCO 2 ‐extracted oil were two to four times greater than solvent‐ and UAAE‐extracted oils, respectively. The superiority of SCO 2 in extracting the tocol components from plant materials was reported by Chia et al, in which their study demonstrated the tocols content of SCO 2 ‐extracted rice bran oil was ten times greater than solvent‐extracted rice bran oil. Low level of tocopherols content in UAAE‐extracted oil may be the poor solubility of non‐polar tocopherols in a polar solvent (e.g., water).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Results indicated the tocol composition of avocado oil was significantly affected ( p < 0.05) by extraction methods, whereby the contents of α‐ and γ‐tocopherols of SCO 2 ‐extracted oil were two to four times greater than solvent‐ and UAAE‐extracted oils, respectively. The superiority of SCO 2 in extracting the tocol components from plant materials was reported by Chia et al, in which their study demonstrated the tocols content of SCO 2 ‐extracted rice bran oil was ten times greater than solvent‐extracted rice bran oil. Low level of tocopherols content in UAAE‐extracted oil may be the poor solubility of non‐polar tocopherols in a polar solvent (e.g., water).…”
Section: Resultsmentioning
confidence: 74%
“…Previous studies indicated that solvents, temperatures, and time used in oil manufacturing process can significantly affect the qualities, bioactive phytochemicals, volatile components, and antioxidant capacities of plant oils . There is an increased interest in the development of oil extraction technologies that preserve the nutritional characteristics of virgin avocado oil.…”
Section: Introductionmentioning
confidence: 99%
“…A schematic diagram of the subCO 2 soxhlet extraction process used in this study is shown in Figure as described by Chia et al (). In this process, the liquid CO 2 collected from the condenser flowed into the vessel to start the extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike supercritical CO 2 extraction, an oil extracted via subcritical CO 2 is usually lighter in colour and contains fewer waxes and resins. The mild temperature and pressure used in subcritical fluid extraction with CO 2 are able to retain most of the thermally sensitive bioactive components in the plant materials . In comparison to solvent extraction, the avocado oils extracted by subcritical CO 2 were found to have higher iodine values, but lower slip melting points, FFA contents and saponification values…”
Section: Avocado Oil Extraction Processesmentioning
confidence: 99%